Analisis Kesulitan Siswa Slow Learner dalam Proses Conjecturing di SMPN 11 Mataram pada Materi Pola Bilangan - Mely Andayani; Sutarto; Ade Kurniawan (Jurnal Kependidikan Ki Hajar Dewantara, 2026)
This study aims This study aims to examine the difficulties faced by slow learner students in the conjecturing process at SMPN 11 Mataram on the topic of number patterns. The research method used is qualitative with a descriptive approach. The subjects of this study are 5 students categorized as slow learners based on the IQ test conducted by a psychological consultation and testing agency using the culture fair intelligence test. Data were collected using supporting instruments, namely number pattern problem sheets and interviews. The data analysis techniques employed include data collection, data reduction, data display, and conclusion drawing and verification. The results of the study show that slow learner students face difficulties in the conjecturing process in solving number pattern problems after passing the stages of observing the case, organizing the case, searching for patterns, and predicting the patterns. At the stage of searching and predicting the pattern, 2 students identified the difference in the formed pattern, while 3 students did not understand the intent of the problem, which caused difficulties in advancing to the formulation of the conjecture, as they could not connect the difference with the general formula. It can be concluded that the difficulties faced by slow learner students in the process occur because the students find it hard to distinguish between the general formula and the specific formula, leading to confusion and an inability to determine the next number in the given pattern. This study provides insights for educators to design more effective teaching strategies for slow learner students, particularly in understanding number pattern concepts through a more concrete approach.